The 2030 spike : countdown to global catastrophe - Mason, Colin, 1926-2020 (Earthscan Publications, 2003)
The clock is relentlessly ticking! Our world teeters on a knife-edge between a peaceful and prosperous future for all and a dark winter of death and destruction that threatens to smother the light of civilization. Within 30 years in the 2030 decade six powerful 'drivers' will converge with unprecedented force in a statistical spike that could tear humanity apart and plunge the world into a new Dark Age. Depleted fuel supplies massive population growth poverty global climate change famine growing water shortages and international lawlessness are on a crash course with potentially catastrophic c.